2013
DOI: 10.1016/j.fct.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and genoprotective effects of spent coffee extracts in human cells

Abstract: Abbreviations:8-oxoguanine, 8-oxoGua; DAPI, 4,6-diamidino-2-phenylindole; FPG, formamidopyrimidine DNA glycosylase; H 2 DCF-DA, 2´, 7´-dichlorfluoresceindiacetate; H 2 O 2 , hydrogen peroxide; MTT, (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide); ROS, reactive oxygen species; SBs, strand breaks. 1 AbstractSpent coffee has been shown as a good source of hydrophilic antioxidant compounds.The ability of two spent coffee extracts rich in caffeoylquinic acids, mainly dicaffeoylquinic acids, and caffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
3
34
0
1
Order By: Relevance
“…Previous study by Bagdas et al [25] reported that systematical CGA application in skin flap surgeries can accelerate healing and flap survival in animal of wound healing delay by diabetic condition. It has been also suggested that topically CGA ointment has a potent wound healing effect on nondiabetics rats [26]. Thus, our results are consistent with previous reports in literature.…”
Section: Resultssupporting
confidence: 93%
“…Previous study by Bagdas et al [25] reported that systematical CGA application in skin flap surgeries can accelerate healing and flap survival in animal of wound healing delay by diabetic condition. It has been also suggested that topically CGA ointment has a potent wound healing effect on nondiabetics rats [26]. Thus, our results are consistent with previous reports in literature.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have highlighted a higher content of antioxidant and bioactive compounds in Arabica and Robusta spent coffee extracts compared with their respective coffee brews (Bravo et al, 2012(Bravo et al, , 2013. Our study demonstrated the high levels of unextracted CGAs in spent Arabica and Robusta coffee compared with the brews, and showed that the aqueous extracts of spent coffee were stable under gastrointestinal conditions and as bioaccessible as the compounds found in coffee beverage.…”
Section: Resultssupporting
confidence: 42%
“…Arabica and Robusta coffees are the most consumed varieties. Previously it was shown that the spent coffees obtained after the preparation of a filter (Arabica coffee) and an espresso (Robusta coffee) coffee brew had the highest antioxidant activity in chemical-based assays and in cell cultures (Bravo et al, 2012(Bravo et al, , 2013. Thus, the two spent coffees were used to prepare extracts which were lyophilized, stored, and reconstituted prior to analysis and testing, along with their respective coffee brews.…”
Section: Characterization Of Spent Coffee Extractsmentioning
confidence: 99%
“…Cell viability was determined by assessing the reduction of MTT to formazan by the mitochondrial enzyme as described (Bravo et al, 2013). Stock solutions of mycotoxins were prepared in methanol.…”
Section: Mtt Assaymentioning
confidence: 99%